Pengaruh Pola Komunikasi Demokratis Orang Tua terhadap Perkembangan Interaksi Sosial pada Anak - Ruzea, Iryne; Aliza, Nur; Afandes, Muhammad Farhan; Yulianti, Yulianti (Universitas Mathla'ul Anwar Banten, 2023)
The writing of this Literature review is based on the existence of various problems of social development stages in children and parental communication patterns in Indonesia, which are still not entirely positive, inappropriate and effective for development and children's growth, including children's social development such as children who are not brave, nervous and even cry if they are going to communicate and interact with other people or society. This literature review aims to analyze and see specifically and theoretically how the influence of democratic parental communication patterns on one of the child's developmental tasks, namely the development of children's social interactions with the surrounding environment. The method in this literature review was carried out on six articles obtained by researchers from one database, namely Google Scholar. The keywords used to search for this article were